2019
DOI: 10.1002/ldr.3267
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing soil physical quality and cotton yields through diversification of agricultural practices in central Brazil

Abstract: Brazil plays an important role in the global agricultural production, making Brazilian productive land use and management a critical issue. This study tested the hypothesis that soil physical quality (SPQ) of the Cerrado biome in central Brazil depends on appropriate crop rotation and tillage practices in cotton (Gossypium hyrsutum [L.])‐based cropping systems and is critical to achieve optimal cotton yields (COT). SPQ of an Oxisol was accessed for layers of 0.0–0.1, 0.1–0.2, and 0.2–0.4 m under conventional t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 62 publications
2
18
0
2
Order By: Relevance
“…The results reported in this study showed that HA promoted positives effects on maize, and guaranteed a residual Zn for brachiaria plants grown in sequence to maize, in a soil type-dependent way. However, maize–brachiaria cultivated in a sequence is widely performed in Brazilian cropping areas [ 3 ]; there is no study reporting how HA-Zn interaction exerts influence on the brachiaria cultivated in sequence to maize. Evaluating only the effect of HA-Zn interaction in single cultivation of coffee seedlings, Just et al [ 10 ] reported that the application of 50 mg kg −1 C-HA increased the solution Zn in alkalinized soils (pH > 7.2), probably due to the Zn–HA complexation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results reported in this study showed that HA promoted positives effects on maize, and guaranteed a residual Zn for brachiaria plants grown in sequence to maize, in a soil type-dependent way. However, maize–brachiaria cultivated in a sequence is widely performed in Brazilian cropping areas [ 3 ]; there is no study reporting how HA-Zn interaction exerts influence on the brachiaria cultivated in sequence to maize. Evaluating only the effect of HA-Zn interaction in single cultivation of coffee seedlings, Just et al [ 10 ] reported that the application of 50 mg kg −1 C-HA increased the solution Zn in alkalinized soils (pH > 7.2), probably due to the Zn–HA complexation.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding tolerance to Zn, maize ( Zea mays ) is highly sensitive, while some grass plants such as brachiaria are less affected by low levels of Zn in the growth media [ 2 ]. The maize–brachiaria cultivation sequence is adopted in many Brazilian cropping areas [ 3 ]. The efficient use and adequate Zn fertilization are key issues to increase food production in Brazilian soils [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…No-tillage (NT), an incipient management system used in Brazilian paddy fields, consists of sowing beneath cover crops residues on the soil surface. NT enhances both the soil chemical (L. H. C. Souza et al, 2018) and physical structure (Anghinoni, Tormena, Lal, Zancanaro, & Kappes, 2019). The microenvironmental changes caused by NT increase microbial biomass and decrease the metabolic quotient (da Silva et al, 2014).…”
mentioning
confidence: 99%
“…Biopores can even drive the root development for the subsequent crop (Han et al, 2015(Han et al, , 2016. Another important topic is that crop diversification adds crop residues differing in quantity and quality, often resulting in increased biochemical interactions between plants and soil microorganisms (Reich et al, 2012;Pires et al, 2020;Venter et al, 2016), alleviating soil compaction, and improving soil structure and water infiltration (Anghinoni et al, 2019;Blanco-Canqui et al, 2015). Soil structure drives critical processes and functions in the environment (Bronick & Lal, 2005;Rabot et al, 2018).…”
Section: Core Ideasmentioning
confidence: 99%